IDENTIFIKASI ZONA RESERVOAR PANAS BUMI BERDASARKAN ANALISIS FAULT FRACTURE DENSITY CITRA DIGITAL ELEVATION MODEL ALOS PALSAR DI GUNUNG RAJABASA: IDENTIFICATION OF GEOTHERMAL RESERVOIR ZONE BASED ON FAULT FRACTURE DENSITY ANALYSIS OF DIGITAL ELEVATION MODEL ALOS PALSAR IMAGE IN MOUNT RAJABASA - Darmawan, I Gede Boy; Fahlevi, Dirga Ilham; Yassar, Muhammad Farhan; Pramudya, Fachri Aldi (Buletin Sumber Daya Geologi, 2021)
Mount Rajabasa is one of the geothermal fields in Sumatra that has not been exploited until now. The existence of manifestations in this area is an indication of the potential existence of geothermal reservoirs. This study aims to identify high permeability zones based on Fault Fracture Density (FFD) analysis and to analyze the relationship between the characteristics of the geothermal fluid path structure to the surface and the potential location of the geothermal reservoir. The FFD method is carried out using the Digital Elevation Model (DEM) ALOS PALSAR image to map the lineaments associated with fault zones and fractures, especially in the manifestation area. Field observations were made to confirm the FFD results. The dominant direction of the identified structures is partially aligned and in line with the Sumatra fault system, namely the northwest-southeast direction and partly shows a response that intersects the main fault system. Furthermore, the results of the FFD analysis show a significant relationship between the weak zone (fracturing) and the geothermal reservoir zone as indicated by the high structural density pattern in the upflow zone in the Way Sulfur manifestation, while the outflow zone in the hot springs of Mount Botak is at a low structural density.